Review about Joaquín Oliver Pozo: The Inspection of Education of Andalusia. Origin, development and intervention in the centers - Gomera López, Francisco A. (Avances en Supervisión Educativa, 2015)
Autor: Joaquín Oliver PozoEditorial: MADAño de edición: 2015Páginas: 466Formato papel: Tapa blanda, 15x 23 cm.ISBN (en papel): 9788467673029